Coleoptera of Brazil: what we knew then and what we know now. Insights from the Catálogo Taxonômico da Fauna do Brasil - Caron, Edilson (2024)
In 2000, Cleide Costa published a paper presenting the state of knowledge of the Neotropical Coleopte-ra, with a focus on the Brazilian fauna. Twenty-four years later, thanks to the development of the Coleoptera section of the Taxonomic Catalog of the Brazilian Fauna (CTFB – Catálogo Taxonômico da Fauna do Brasil) through the collaboration of 100 coleopterists from all over the globe, we can build on Costa’s work and present an updated overview of the state of knowledge of the beetles from Brazil. There are currently 35,699 species in 4,958 genera and 116 families known to occur in the country, including representatives of all extant suborders and superfamilies. Our data show that the Brazilian beetle fauna is the richest on the planet, concentrating 9% of the world species diversity, with some estimates accounting to up to 15% of the global total. The most diverse family in numbers of genera is Cerambycidae (1,056 genera), while in number of species it is Chrysomelidae (6,079 species). Conotrachelus Dejean, 1835 (Curculionidae) is the most species-rich genus, with 570 species. The French entomologist Maurice Pic is the author who has contributed the most to the naming of species recorded from Brazil, with 1,794 valid names in 36 families, whereas the Brazilians Ubirajara R. Martins and Maria Helena M. Galileo are the only ones among the top-ten authors to have named species in the 21st century. Currently, approximately 144 new species of Brazilian beetles are described each year, and this average is projected to increase in the next decade to 180 species per year, or about one new Brazilian beetle every two days.